Informing a governance model for integration of community pharmacists and family physicians and nurse practitioner-led practices and teams within Ontario Health Teams: A protocol - Monica Aggarwal; Lisa Dolovich; Yazid Al Hamarneh; Kristina M. Kokorelias; Reed Beall; Ross Upshur (PLoS ONE, 2025)
Background The expansion of the scope of practice for community pharmacists has the potential to improve timely access to primary care. However, overlapping scopes of practice with family physicians (FPs) and nurse practitioners (NPs) have the potential for duplication of services or fragmented care. To optimize the benefits of this change, clear integrated governance mechanisms are needed to define roles, responsibilities, and accountabilities between providers. To date, there is no research on integrated governance models for independent primary care provider organizations. Objective To develop a governance model that will enable better integration of community pharmacists with FPs and NPs within Ontario Health Teams. Methods A multi-method study design will be used. A literature review will be conducted to identify innovative programs and policies between community pharmacies, FPs, and NPs. Then, relevant stakeholders will be identified and engaged in key informant interviews to exchange knowledge, identify priorities, and co-create policy and governance strategies. Results The scoping review will identify existing models, gaps, and governance approaches that support or hinder integration. Interviews will explore stakeholder experiences related to integrated governance. A conceptual integrated governance model will be developed based on these findings. Discussion This initiative aligns with the broader mission of improving healthcare services and outcomes in Ontario by establishing a governance model that enables better integration between community pharmacists, FPs, and NPs. This research will support policy and practice innovations to strengthen integrated delivery in Ontario and beyond.